Point-of-care tests for the diagnosis of Neisseria gonorrhoeae infection: a systematic review of operational and performance characteristics. Issue 4 (23rd October 2012) - Watchirs Smith, Lucy Alexandra; Hillman, Richard; Ward, James; Whiley, David M; Causer, Louise; Skov, Steven; Donovan, Basil; Kaldor, John; Guy, Rebecca
Abstract : Objectives: Systematic review of the performance and operational characteristics of point-of-care (POC) tests for the diagnosis of Neisseria gonorrhoeae . Methods: We searched PubMed and Embase until August 2010 using variations of the terms: 'rapid test', ' Neisseria gonorrhoeae ' and 'evaluation'. Results: We identified 100 papers, 14 studies were included; nine evaluated leucocyte esterase (LE) dipsticks and three immunochromatographic strips, and two clinical audits of microscopy were identified. Of the field evaluations the gold standard was nucleic acid amplification technology in six studies and bacterial culture in the other six. In four studies, 50% or more of the patients were symptomatic. The median sensitivity of LE dipsticks was 71% (range 23–85%), median specificity was 70% (33–99%), median positive predictive value (PPV) was 19% (5–40%) and median negative predictive value (NPV) was 95% (56–99%). One LE study found a sensitivity of 23% overall, increasing to 75% in symptomatic women. LE dipsticks mostly involved three steps and took under 2 min. The median sensitivity of immunochromatographic tests (ICT) was 70% (60–94%), median specificity was 96% (89–97%), median PPV was 56% (55–97%) and median NPV was 93% (92–99%). Immunochromatic strips involved five to seven steps and took 15–30 min. Specificity of microscopy ranged from 38% to 89%. Conclusions: ICT and LE tests had similar sensitivities, but sensitivity results may be overestimated as largely symptomatic patients were included in some studies. ICT had a higher specificity in women than LE tests. The findings highlight the need for improved POC tests for diagnosis of N gonorrhoeae and more standardised evaluations.